Huawei / Hani Arina Mohd Subri - Mohd Subri, Hani Arina (2022)
This assignment is about identifying the problems with the product. The company that I have chosen is Huawei Technologies. From their products variety, I have chosen the Watch Fit wearable to do my analysis and findings. In this case study, I have done SWOT analysis to identify the strength, weakness, opportunities, and threats of the Watch Fit. The main problem that I have identified on this Watch Fit is that it has limited music management, unlike the other products by Huawei such as their smartphones, tablets, laptops and desktops. From the problem, I can come up with the best solution which is installing loudspeaker and microphone on the Watch Fit just like the smartphones, tablets, laptops and desktops.